Does offshoring boost productivity? A comparison of SMEs and large firms for Germany - Kreutzer, Fabian; Berger, Wolfram (Economics and Business Letters, 2022)
We use plant-level evidence for Germany to explore the productivity effects of offshoring of small and medium-sized enterprises (SME) and compare them to those derived for a sample of large companies. SMEs usually face tighter resource constraints than larger companies, thus making it harder for them to reap the potential productivity gains associated with offshoring. We find evidence for the group of SMEs that plants that offshore business activities tend to be among the more productive ones, ex ante. However, offshoring plants lose this edge over their non-offshoring counterparts. The initial productivity gap is reversed, and the productivity of offshoring plants lags behind even several years after offshoring has actually taken place. Neither observation can be confirmed for large companies.